2014
DOI: 10.1111/cen.12444
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adrenal function in critically ill children

Abstract: SummaryObjective There is no consensus on adequate adrenal response to critical illness. We aimed to evaluate adrenal function in critically ill children and its association with clinical outcome. We hypothesized that salivary cortisol would be a more appropriate tool to evaluate adrenal function in critically ill children. Methods This was a prospective cohort study. The concentrations of serum total and salivary cortisol were measured in 34 critically ill children before and after stimulation with 250 lg adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
3
16
0
1
Order By: Relevance
“…In our study, the prevalence of CIRCI was 18.5% in comparison to 25.0% in another study on PICU patients with pediatric acute lung injury/acute respiratory distress syndrome 25 and 39.6% and 44.4% in patients with severe sepsis and septic shock respectively 26 . In addition, our study found no association between CIRCI and the reported mortality rate in accordance with a previous study 27 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the prevalence of CIRCI was 18.5% in comparison to 25.0% in another study on PICU patients with pediatric acute lung injury/acute respiratory distress syndrome 25 and 39.6% and 44.4% in patients with severe sepsis and septic shock respectively 26 . In addition, our study found no association between CIRCI and the reported mortality rate in accordance with a previous study 27 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with previous data indicating that critically ill children have higher salivary cortisol concentrations. 23 In addition, in this cohort, extremely high concentrations of sAA were observed, although considerable variation in levels was noted ( Table 3 ). Indeed, in our cohort, although levels of SIgA were significantly higher when compared to those reported in healthy children 25 , 26 ( Table 1 ), a significant variation was observed ( Table 3 ).…”
Section: Discussionmentioning
confidence: 67%
“…Most recently, Starzak et al 25 reported a median level of 2.439 ± 1.192 mg/dL. Regarding critically ill children, Balbao et al 23 reported values ranging between 7.7 and 448.3 nmol/L for salivary cortisol in children aged 0.5–8.3 years. Our results are in accordance with previous data indicating that critically ill children have higher salivary cortisol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Because diagnostic criteria of relative adrenal insufficiency (RAI) vary, it is difficult to accurately determine the incidence rate of RAI after congenital heart surgery. Although the ACTH stimulation test can be used to assess adrenal function based on the hypothalamic-pituitary-adrenal axis reactivity, this approach is used primarily to assess reserve capacity of adrenal function rather than synthesis and secretion of adrenocortical hormone [ 19 , 20 ], and ethically, the ACTH stimulation test cannot verify whether RAI occurred.…”
Section: Discussionmentioning
confidence: 99%